2021
DOI: 10.1038/s41598-021-99521-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation of adult skeletogenesis in starfish and modifications during gene network co-option

Abstract: The larval skeleton of the echinoderm is believed to have been acquired through co-option of a pre-existing gene regulatory network (GRN); that is, the mechanism for adult skeleton formation in the echinoderm was deployed in early embryogenesis during echinoderm diversification. To explore the evolutionary changes that occurred during co-option, we examined the mechanism for adult skeletogenesis using the starfish Patiria pectinifera. Expression patterns of skeletogenesis-related genes (vegf, vegfr, ets1/2, er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 44 publications
(72 reference statements)
2
22
0
1
Order By: Relevance
“…As the MAPK signaling pathway is activated cell-autonomously in the early embryo, possibly through the actions of localized maternal factors such as β-catenin (Fernandez-Serra et al, 2004; Röttinger et al, 2004), we proposed that the heterochronic shift in the deployment of the skeletogenic GRN that occurred during euechinoid evolution was achieved by an important evolutionary innovation that placed MAPK signaling under maternal control. We favor a model whereby current regulatory mechanisms that underlie late embryonic skeletal patterning and growth reflect an ancient heterochronic shift in VEGF3 expression by ectodermal cells (Morino et al, 2012; Yamazaki et al, 2021). We hypothesize that VEGF3 activates Ets1 through the MAPK signaling pathway at late embryonic stages, circuitry that is likely to be similar to the ancestral skeletogenic GRN found in the adult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the MAPK signaling pathway is activated cell-autonomously in the early embryo, possibly through the actions of localized maternal factors such as β-catenin (Fernandez-Serra et al, 2004; Röttinger et al, 2004), we proposed that the heterochronic shift in the deployment of the skeletogenic GRN that occurred during euechinoid evolution was achieved by an important evolutionary innovation that placed MAPK signaling under maternal control. We favor a model whereby current regulatory mechanisms that underlie late embryonic skeletal patterning and growth reflect an ancient heterochronic shift in VEGF3 expression by ectodermal cells (Morino et al, 2012; Yamazaki et al, 2021). We hypothesize that VEGF3 activates Ets1 through the MAPK signaling pathway at late embryonic stages, circuitry that is likely to be similar to the ancestral skeletogenic GRN found in the adult.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the causal links required for the construction of experimental GRN models, functional perturbations of regulatory genes are usually performed, followed by observation of the effects on potential target genes. Although several approaches have been employed to successfully perturb gene function in sea urchin embryos, functional studies generally rely on microinjection of reagents such as morpholino antisense oligonucleotides (MOs) to block translation or splicing (Yaguchi, 2019), mRNAs encoding dominant-negative or constitutively active forms of proteins (Lepage and Gache, 2004), and targeted genome editing nucleases, such as transcription activator-like effector nucleases (TALENs) (Yamazaki et al, 2021) and CRISPR-Cas9 (Fleming et al, 2021; Lin et al, 2019; Wessel et al, 2020). These conventional approaches, however, face a common constraint.…”
Section: Introductionmentioning
confidence: 99%
“…As components of a single GRN are interconnected, differences in spatio-temporal expression of particular regulatory gene can potentially affect its downstream effectors, allowing for their redeployment in the novel context. The examples of such evolutionary co-options are widespread in both animals [63][64][65] and plants [66][67][68]. As FUMs might evolve through heterochronic changes in FM genetic patterning, the co-option of multiple components of flower-specific GRN can tentatively explain the origin of some novelties associated with floral units, including formation of pseudanthia.…”
Section: Floral Unit Meristems-an Important Preadaptation For Pseudan...mentioning
confidence: 99%
“…2,3 Among echinoderms, starfish have been used to investigate various developmental phenomena such as whole-body regeneration, germline formation, and early specification. [4][5][6][7][8][9][10][11][12][13][14] For example, gene regulatory networks (GRNs) of early specification have been unraveled in starfish embryos and compared with other echinoderms to elucidate the evolutionary transition of GRN circuits. 5,6,[8][9][10][11][12]14 It is also revealed that starfish larval regeneration is regulated by an evolutionarily conserved machinery across the animal kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] For example, gene regulatory networks (GRNs) of early specification have been unraveled in starfish embryos and compared with other echinoderms to elucidate the evolutionary transition of GRN circuits. 5,6,[8][9][10][11][12]14 It is also revealed that starfish larval regeneration is regulated by an evolutionarily conserved machinery across the animal kingdom. 4 Overall, molecular study of starfish embryos has received considerable attention in recent years.…”
Section: Introductionmentioning
confidence: 99%